Isolation, characterization and identification of sponge-associated bacteria producing antimicrobial compounds - RISKY HADI WIBOWO; SIPRIYADI SIPRIYADI; WELLY DARWIS; DELFIANI ANGGIAS PUTRI; SALPRIMA YUDHA; MASHUDI MASHUDI; NOOR ANDRYAN ILSAN; PERSON PESONA RENTA (Society for Indonesian Biodiversity, 2023)
Abstract. Wibowo RH, Sipriyadi, Darwis W, Putri DA, Yudha S, Mashudi, Ilsan NA, Renta PP, Masrukhin. 2023. Isolation, characterization and identification of sponge-associated bacteria producing antimicrobial compounds. Biodiversitas 24: 3616-3623. Sponges are marine biota that is currently in great demand as research object. Sponges also belong to a group of marine life that has symbiotic with bacteria. Bacteria that have formed a symbiotic relationship with a sponge may produce secondary metabolites that protect their host from pathogens. This study aimed to isolate, select, characterize and identify bacteria associated with the sponge Aplysina sp. that exhibit antimicrobial activity. The methods used in this study were bacterial isolation, screening, molecular identification, and observing their ability to produce antimicrobial compounds. A total of 16 isolates were isolated on the Sea Water Complete agar medium, and four isolates were able to inhibit the growth of pathogenic microbes including Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans. Four isolates with the most significant inhibitory clear zones were selected for further testing. The isolate APD10 showed the biggest inhibition zone. The molecular identification results showed that the APD3 and APD15 had genetic similarities with Bacillus subtilis, isolate APD9 had genetic similarities with Bacillus paralicheniformis, and isolate APD10 had genetic similarities with Bacillus velezensis. Two isolates (APD3 and APD15) gene sequences for the KS domain in PKS were related to polyketide synthase, while APD10 in KS was related to oxidoreductase. Two isolates (APD3 and APD15) gene sequences encoding domain A on NRPS had a relationship with a bioactive compound in the form of surfactin, APD9 was related to a bioactive compound in the form of bacitracin, and APD10 NRPS was related to adenylation.